SYSTEMATIC POSITION OF FERONIA COGNATA DEJEAN, 1831 (COLEOPTERA, CARABIDAE) - Guéorguiev Borislav V.; Giachino, Pier Mauro (Fragmenta entomologica, 2008)
The type material of Feronia cognata Dejean, 1831, Steropus schmidtii Chaudoir, 1838 and Pterostichus placidus W. Rosenhauer, 1847 is examined. This action resulted into new combinations, new synonym, and restored status in terms of the genera Pterostichus Bonelli, 1810 and Tapinopterus Schaum, 1858: Tapinopterus (Tapinopterus) cognatus (Dejean, 1831), comb. nov. of Pterostichus (Pseudosteropus) cognatus (Dejean, 1831); Tapinopterus (Tapinopterus) kaufmanni Ganglbauer, 1896, syn. nov. of Tapinopterus (Tapinopterus) cognatus (Dejean, 1831); Tapinopterus (Tapinopterus) cognatus transsylvanicus Mandl, 1936, comb. nov. of Tapinopterus (Tapinopterus) kaufmanni transsylvanicus Mandl, 1936; Tapinopterus (Tapinopterus) cognatus kalofirensis Maran, 1933, comb. nov. of Tapinopterus (Tapinopterus) kaufmanni kalofirensis Maran, 1933; Tapinopterus (Tapinopterus) cognatus winkleri Mandl, 1936, comb. nov. of Tapinopterus (Tapinopterus) kaufmanni winkleri Mandl, 1936; Steropus schmidtii Chaudoir, 1838 removed from synonymy with Feronia cognata Dejean, 1831 and treated as valid species - Pterostichus (Pseudosteropus) schmidtii (Chaudoir, 1838), stat. rest. Lectotype and paralectotypes for Steropus schmidtii Chaudoir, 1838 are designated.